Total branching ratio of the K− two-nucleon absorption in 12C. (10th July 2020) - Del Grande, R; Piscicchia, K; Cargnelli, M; Curceanu, C; Fabbietti, L; Marton, J; Moskal, P; Ramos, A; Scordo, A; Sirghi, D; Skurzok, M; Doce, O Vazquez; et al.
Abstract: This work is a critical re-analysis of the results obtained by the AMADEUS collaboration, concerning the measurement of the K − multi-nucleon absorption reactions, on a 12 C target, in the Λp final state (Del Grande et al 2019 Eur. Phys. J. C 79, 190). We show that a good estimate of the K − two-nucleon absorption total branching ratio can be extracted, given that the measured final state interactions and conversion reactions contain information on almost all the remaining hyperon-nucleon final state combinations. The main contribution to the total branching ratio of the K − two-nucleon absorption in Carbon is extracted from the measured ratios and is found to be ( 16.1 ± 2.9 ( stat . ) − 5.5 + 4.3 ( syst . ) ) %, which is in agreement with recent theoretical predictions. The missing contribution, from those few channels for which a Λp pair could not be detected in the final state of the interaction, is also estimated combining both the measured branching ratios and the available theoretical information, and amounts to ( 5.5 ± 0.1 ( stat . ) − 0.9 + 1.0 ( syst . ) ) % . All together the total branching ratio of the K − two-nucleon absorption in Carbon is found to be ( 21.6 ± 2.9 ( stat . ) − 5.6 + 4.4 ( syst . ) ) % .